2020
DOI: 10.2147/opth.s256755
|View full text |Cite
|
Sign up to set email alerts
|

<p>Individual Macular Layer Evaluation with Spectral Domain Optical Coherence Tomography in Normal and Glaucomatous Eyes</p>

Abstract: Purpose: To evaluate differences in the thickness of the individual macular layers between early, moderate, and severe glaucomatous eyes and compare them with healthy controls. Patients and Methods: Subjects with glaucoma presenting typical optic nerve head findings, high intraocular pressure with or without visual field (VF) damage and normal controls were included. All participants underwent 24-2 perimetry and spectral-domain OCT. Patients were divided into three groups (early, moderate, and severe) based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
(77 reference statements)
0
9
1
Order By: Relevance
“…Previous studies investigating macular retinal layer thickness measurements in glaucoma have variably reported no significant differences in INL and outer retinal thicknesses between glaucoma and comparative cohorts [10][11][12][13][14][15] and increased INL thickness with increasing glaucoma severity. 13,[16][17][18] Conversely, this study observed colocalised reductions in INL and GCIPL thickness, and two key points have likely contributed to these differences between study findings.…”
Section: Comparison To Existing Literaturementioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies investigating macular retinal layer thickness measurements in glaucoma have variably reported no significant differences in INL and outer retinal thicknesses between glaucoma and comparative cohorts [10][11][12][13][14][15] and increased INL thickness with increasing glaucoma severity. 13,[16][17][18] Conversely, this study observed colocalised reductions in INL and GCIPL thickness, and two key points have likely contributed to these differences between study findings.…”
Section: Comparison To Existing Literaturementioning
confidence: 83%
“…8 Whether retinal layers outside of the inner retina are affected in glaucoma is not well-established, with OCTbased studies in glaucomatous eyes variably reporting no changes in outer retinal thickness measurements and apparent thickening of outer retinal measurements with increasing glaucoma severity. [9][10][11][12][13][14][15][16][17][18] The myriad of presentations consistent with glaucoma has likely contributed to widely variable thickness measurements between individual eyes with glaucoma and between cohorts in different studies, 19,20 and likewise it is well-documented that retinal thickness measurements in normal eyes are highly variable. [21][22][23][24][25] Subsequently, when not accounting for variations across individuals, significant overlap in thickness measurement distributions could occur depending on effect size.…”
mentioning
confidence: 99%
“…(22) Until now, no studies have described the ONL layer in symptomatic carriers with LHON. Recently, Fujihara et al (23) published a study on glaucoma that found signi cant thinning of the ONL in advanced open-angle glaucoma. It has also been reported that macular ONL thickness increases in the early stages of glaucoma, then gradually thins in the later stages until the thickness approached that of normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It makes it possible to diagnose and monitor glaucoma through the evolution of macular thickness. Although central vision is often preserved in late glaucoma, the thinning of the macular area is a parameter found in the early stages of the disease and precedes visual field defects [18]. Figure 1 exemplifies an OCT diagram (left part) correlating with a papilla (right part).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%